Effectiveness of Tongkol Fish Bone Flour (Auxis rochei) on the Molting Frequency of Freshwater Lobster Seed (Cherax quadricarinatus) - Dian Lestari; Nur Wapra; Rahmi Nur; Muh. Ansar; Muhammad Nur; Nur Indah Sari Arbit; Fauzia Nur (Jurnal Sains dan Teknologi Perikanan, 2026)
Freshwater lobsters are one of the fishery commodities that are now widely cultivated because they are rich in nutrients such as biotin, calcium, iron, niacin, phosphorus, protein, vitamins A, B6, and B12. This study aims to determine the effectiveness of skipjack tuna (Auxis rochei) bone meal on the molting frequency of freshwater lobster (Cherax quadricarinatus) fry. This study was conducted in August 2024 at CV. Cova Aquaculture, Tande Timur Village, Banggae Timur Subdistrict, Majene Regency. The test animals used were freshwater lobster fry measuring ±2 cm, aged 1 month, with an average weight of 0.50 g. The feed used was Feng li with a protein content of 40%, combined with tongkol fish bone meal with a protein content of 29.49% and calcium of 12.66%. This study used a completely randomized design with 4 treatments and 3 replicates each, including treatment A with a 0% fish bone meal dose (control), treatment B with a 2% fish bone meal dose, treatment C with a 4% fish bone meal dose, and treatment D with a 6% fish bone meal dose. Data analysis was performed using one-way ANOVA with the assistance of SPSS software. The results showed that the effectiveness of tuna bone meal had a significant effect on the molting frequency of freshwater lobster seeds, but did not have a significant effect on the average absolute weight growth and survival rate. The best molting frequency was obtained in treatment C with a 4% dose of tuna bone meal, which was 1.4%.